2023
DOI: 10.3390/jmse11051074
|View full text |Cite
|
Sign up to set email alerts
|

Research on Seabed Sediment Classification Based on the MSC-Transformer and Sub-Bottom Profiler

Abstract: This paper proposed an MSC-Transformer model based on the Transformer’s neural network, which was applied to seabed sediment classification. The data came from about 2900 km2 of seabed area on the northern slope of the South China Sea. Using the submarine backscattering intensity and depth data obtained by the sub-bottom profiler, combined with latitude and longitude information, a seabed dataset of the slope area of the South China Sea was constructed. Moreover, using the MSC-Transformer, the accurate identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Luo et al compared the classification performance of deep and shallow CNN models for three types of sediment, namely stone, mud, and sand, and found that the shallow CNN model outperformed the deep CNN model while achieving excellent classification performance [22]. Wang et al conducted a study on sediment classification using MSC-Transformer and shallow formation profile data and achieved good results [23]. Additionally, Tegowski extracted features such as fractal dimension and spectral length of backscatter images as K-means clustering parameters for classification [24].…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al compared the classification performance of deep and shallow CNN models for three types of sediment, namely stone, mud, and sand, and found that the shallow CNN model outperformed the deep CNN model while achieving excellent classification performance [22]. Wang et al conducted a study on sediment classification using MSC-Transformer and shallow formation profile data and achieved good results [23]. Additionally, Tegowski extracted features such as fractal dimension and spectral length of backscatter images as K-means clustering parameters for classification [24].…”
Section: Introductionmentioning
confidence: 99%